Purification and Characterization of Chitinase from the Nematode – Fungus Paecilomyces sp. P1 - Binh, Chu Thanh; Nhue, Nguyen Phuong; Tuyen, Ho; Ha, Bui Thi Viet (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 1DO - 10.25073/2588-1140/vnunst.4851, 2019)
The nematophagous – fungi Paecilomyces sp. are currently developed as a biocontrol agent against plant parasitic nematodes (Khan et al., 2003; Yang et al., 2007). Biological control agents can infiltrate certain nematode sites and destroy them by producing some enzymes including chitinase (Khadijeh et al., 2017). This paper discusses the purification and determination of the chitinase activity from Paecilomyces sp. P1. With Lugol reagent, chitinase of this strain was characterized by diffusion on agar plate. Chitinase specific activity was determined by measuring the release of reducing saccharides from colloidal chitin by the N-acetyl-glucosamine-dinitrosalicylate method at 540 nm. By using the saturated (NH 4 ) 2 SO 4 precipitation at 65% concentration, DEAE A-50 ion exchanges chromatography and SDS - PAGE concentration of 12.5%; chitinase molecules weigh nearly 50kDa, having a specific activity of 133.3 U/mg, 2.1-fold higher than that of supernatant. Furthermore, tested with the nematode Meloidogyne sp., the ability to kill nematodes of Paecilomyces sp. P1 reached 58% efficiency in 96h. These results are a scientific basis for the application of Paecilomyces sp. P1 in the production of nematode insecticides. Keywords Paecilomyces sp. P1 , chitinase, purify, biocontrol, Meloidogyne sp. References [1] Khan Alamgir, Williams Keith, Mark P. Molloy, and Nevalainen Henlena, Purification and characterization of a serine protease and chitinases from Paecilomyces lilacinus and detection of chitinase activity on 2D gels, Protein Expression and Purification. 32 (2003) 210. [2] Khadijeh Abbsi, Doustmorad ZAFARI, Robert WICK., Evaluation of chitinase enzyme in fungal isolates obtained from golden potato cyst nematode Globodera rostochiensis Zemdirbyste-Agriculture. 2 (2017) 179. [3] F. A. Zaki, D. S. Bhatti , Effect of castor (Ricinus communus) and the biocontrol fungus Paecilomyces lilacinus on Meloidogyne javanica, Nematologica. 36 (1980) 114. [4] Z. Perveen, S. Shahzad, A comparative study of the efficacy of Paecilomyces species against root-knot nematode Meloidogyne incognita. Pakistan Journal of Nematology. 31 (2013) 125. [5] P.J.M. Bonants, P.F.L. Fitters, H. Thijs, E. den Belder, C. Waalwijk, J.W.D.M. Henfling. A basic serine protease from Paecilomyces lilacinus with biological activity against Meloidogyne hapla eggs, Microbiology. 141 (1995) 75. [6] D. Wharton,. Nematode eggshells, Parasitology. 81 (1980) 447. [7] C.M Baratto, V. Dutra, J.T. Boldo, L.B. Leiria, MH Vainstein, A. Schrank Isolation, characterization and transcriptional analysis of the chitinase chi2 gene (DQ011663) from the biocontrol fungus Metarhizium anisopliae var. anisopliae., Curr Microbiol. 53 (2006) 217. [8] Van Nam Nguyen, Y.J Kim, K.T Oh, W.J. Jung, R. D Park , The antifungal activity of chitinases from Trichoderma aureoviride DY-59 and Rhizopus microsporus VS-9. Curr. Microbiol. 56 (2008) 28. [9] V. E Tikhonov, L.V Lopez-Llorca, J Salinas, H. B. Jansson . Purification and characterization of chitinases from the nematophagous fungi Verticillium chlamydosporium and V. suchlasporium, Fungal Genet Biol, 2002, 67. [10] R.J. Leger St , R.M. Cooper, A.K. Charnley, Characterization of chitinase and chitobiase produced by the entomopathogenic fungus Metarhizium anisopliae. J. Invertebr. Pathol. 58 (1991) 415. [11] R.S. Patil, V. Ghormade, M.V. Desphande, Chitinolytic enzymes: an exploration. Enzyme Microb. Technol. 26 (2002) 473. [12] J.L.D. Marco, M.C. Valadares-Inglis . Purification and characterization of an N-acetylglucosaminidase produced by a Trichodermaharzianum strain which controls Crinipellis perniciosa. Appl. Microbiol. Biotechnol. 64 (2003) 70. [13] S. Leger, R.J. Joshi, R.J. Bidochka, D.W. Roberts. Characterization and ultrastructural localization of Metarhizium anisopliae, M. xavoviride, and Beauveria bassiana during fungal invasion of host (Manduca sexta) cuticle. Appl Environ Microbiol 62 (1996) 907. [14] S.C Kang, S. Park, D.G Lee, Purification and characterization of a novel chitinase from the entomopathogenic fungus, Metarhiziumanisop liae. J Invertebr Pathol. 73 (1999) 276. [15] Nguyễn Ngọc Châu, Tuyến trùng thực vật và cơ sở phòng trừ, NXB Khoa học Kỹ thuật, Hà Nội, 2003. [16] Kopparapu Narasimha Kumar, Peng Zhou, Shuping Zhang, Qiaojuan Yan, Zhuqing Liu, Zhengqiang Jiang, Purification and characterization of a novel chitinase gene from Paecilomyces thermophila expressed in Escherichia coli. Carbonhydrate Reseach. 347 (2012) 155. [17] J. De la Cruz, A. Hidalgo-Gallego, J.M. Lora, T. Benitez, J.A. Pintor-Toro, A. Llobell , Isolation and characterization of three chitinases from Trichoderma harzianum., Eur. J. Biochem. 206 (1992) 859. [18] Nguyễn Hữu Quân, Vũ Văn Hạnh, Quyền Đình Thi, Phạm Thị Huyền, Tinh sạch và đánh giá tính chất lý hóa của chitinase từ nấm Lecanicillium lecanii, Kỷ yếu Hội nghị Công nghệ Sinh học toàn quốc. 1 (2013) 426. [19] Van Nam Nguyen, In-Jae Oh, Young-Ju Kim, Kil-Yong Kim, Young-Cheol Kim, Ro-Dong Par J Ind., Purification and characterization of chitinases from Paecilomyces variotii DG-3 parasitizing on Meloidogyne incognita eggs. (2009) 195 [20] Methanee Homthong, Anchanee Kubera, Matana Srihuttagum, Vipa Hongtrakul, Isolation and characterization of chitinase from soil fungi, Paecilomyces sp. Agriculture and Natural Resources. 1 (2016) 50. [21] H. M. Hussein Al Ajrami., Evaluation the Effect of Paecilomyces lilacinus as a Biocontrol Agent of Meloidogyne javanica on Tomato in Gaza Strip, Faculty of science Master of Biological Sciences Microbiology, 2016.